Aesthetic Augmentation Phalloplasty: A Systematic Review of Techniques and Outcomes. Issue 5 (November 2020) - Vyas, Krishna S.; Abu-Ghname, Amjed; Banuelos, Joseph; Morrison, Shane D.; Manrique, Oscar
Abstract : Background: Aesthetic augmentation phalloplasty is a set of procedures aimed at increasing penile length and/or girth; many of these procedures are investigational. This systematic review set out to summarize available literature on these procedures in patients with normal penile anatomy. Methods: A systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The MEDLINE/PubMed, Scopus, and Cochrane Databases were used to identify articles on aesthetic augmentation phalloplasty in cis-gender men without penile deformity from 1990 to 2018. Data on outcomes, complications, and patient-reported satisfaction were collected. Results: Sixteen articles, involving 1192 patients, met our inclusion criteria. Mean age ranged from 23 to 44 years, and follow-up time ranged from 6 to 48 months. The quality of the studies was poor regarding methodology for patient selection and outcomes reporting. Surgical interventions included suspensory ligament incision, grafting, flaps, and penile disassembly. Augmentation was performed for length only in 16 percent of patients, girth only in 70.6 percent, and combined in 13.4 percent. Length gain ranged from 8 to 83 percent in the flaccid state and 12 to 53 percent in the erect state. Girth gain ranged from 16 to 56 percent in the flaccid state and 19 to 30 percent in the erect state. The pooled complication rate was 14.6 percent, with those undergoing combined augmentation having the highest complication rate. Patients were generally satisfied; reported satisfaction rates ranged from 50 to 100 percent. Conclusions: Enhancement procedures are controversial and investigational. Data point to inconsistent methodology when reporting penile dimensions, outcomes, and patient satisfaction. Despite the reportedly high satisfaction rates, patients should be counseled regarding high complication rates. Best-practice guidelines will be critical to achieve safe and reliable outcomes.